Analisis Perbedaan Mutu Pelayanan Kesehatan Rawat Jalan Berdasarkan Status Akreditasi dengan Metode Service Quality: Hasil Penelitian - Selvi Hartati; Agus Fitriangga; Widi Raharjo (PT Kalbe Farma Tbk., 2024)
Background: To ensure the universal availability of high-quality health care services, the reform of health systems tried not only to improve the coverage of health care but also the overall quality of health care services. Strategies to improve the quality of health care services include the development of a national accreditation system. This study aims to find out the differences in the quality of outpatient health services based on accreditation status. Methods: The study used a cross-sectional design. The population were all outpatients visiting the GS and the KB community health center with inclusion and exclusion criteria. The sample was selected by accidental sampling. Bivariate analysis using the Mann Whitney U test. Results: A significant difference in empathy (p <0.05), but no significant difference in tangibles, reliability, responsiveness, or assurance (p > 0.05). Conclusion: A significant difference in the quality of outpatient health services in ‘paripurna’ (GS) and ‘utama’ (KB) accredited community health centers is only in the quality of empathy.